World Court's Verdict Towards Bakassi Peninsula: Portraying Gains and Losses - Stephen Achuo Kpwa (Universitas Djuanda, 2022)
Border discords are one of Africa's unending vestiges of European colonialism/imperialism; the Bakassi peninsula dispute between Cameroon and Nigeria was one of such. The subsequent discovery of large deposits of natural resources in the Bakassi region made Cameroon and Nigeria to engage into claims and counterclaims, bilateral diplomacy, military skirmishes, and finally resorting to the World Court or International Court of Justice (ICJ) for judgement. After eight years of deliberations, the court finally adjudged and declared that Bakassi belongs to Cameroon, sparking widespread criticism from Nigeria. Popular opinion in Nigeria held/holds that Nigeria benefited little or nothing following the ICJ verdict of October 10, 2002 and that Cameroon gained exponentially. Thus, the premise of this paper is to outline the gains and losses of both Nigeria and Cameroon following the International Court of Justice’s ruling, and to debunk the Nigerian perception of the verdict being partial and willy-nilly in nature. Using the qualitative method of research, secondary data based on previous research on the Bakassi saga was used. Using content analyses on the secondary data obtained, observations were made on what both Cameroon and Nigeria lost or gained after the World Court's verdict over the Bakassi peninsula. In its findings, this paper proffers that the gains and losses accruing to both countries are evenly distributed. This research can be a springboard for Cameroon and Nigeria to look beyond their gain and losses, and jointly carryout developmental activities in the Bakassi peninsula so as avoid future ethno-nationalistic tendencies in the area